Shadow Banking and Commercial Banks: Mini Review - Josua Panatap Soehaditama; Adler Haymans Manurung; Nera Marinda Machdar (Jurnal Ekonomi dan Bisnis Digital, 2023)
The purpose of this article is to see the relationship between two variables from existing research results with review literature. The method used is qualitative with a literature review of scientific articles looking for relationships between variables used in this article. Literature review sources come from articles from journals, books, and scientific papers. Shadow banking and commercial banks are two things that exist in the banking world today, the results of research on this variable have not been too much so that with the results of research from this article finished adding a different reference and colour even with the description of several scientific articles from journals, books, and others. There is a significant influence from the results of several scientific articles, including (Tang & Wang, 2015), (Tan, 2017), and (Zhu et al., 2019). Other researchers may continue with the same research variables at some other time, and this article does not refute or counter, only add colour to the results.